2006
DOI: 10.1590/s0103-507x2006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de bactérias multiresistentes em um centro de Terapia Intensiva de Hospital brasileiro de emergências

Abstract: Coordenadora do Projeto e Professora Doutora do Departamento de Enfermagem geral e Especializada da EErP-USP 2. graduanda da Escola de Enfermagem de ribeirão Preto-USP e Bolsista PiBiC-CnPq 3. Professor Doutor (ProDoC-CAPES) do Departamento de Enfermagem geral e Especializada EErP-USP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
26

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 9 publications
(10 reference statements)
0
13
1
26
Order By: Relevance
“…The rate of patients colonized with RM during their stay at the ER remained below that of other studies, which reported percentages between 12.98% and 54.3% (13,14) . In bivariate as well as multivariate analysis, colonization by resistant microorganisms was associated with the patient's admission to the ER with community infection and to time of stay at the unit ≥9 days.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…The rate of patients colonized with RM during their stay at the ER remained below that of other studies, which reported percentages between 12.98% and 54.3% (13,14) . In bivariate as well as multivariate analysis, colonization by resistant microorganisms was associated with the patient's admission to the ER with community infection and to time of stay at the unit ≥9 days.…”
Section: Discussioncontrasting
confidence: 58%
“…Colonization is a problem inherent in critically ill patients and a constant public health concern, as it entails severe economic, social and political consequences (12,13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations